The effect of mixed carbon source on enhanced biological phosphorus removal in tropical climate - Cai, Xueyun (2017)
The effectiveness of enhanced biological phosphorus removal (EBPR) is directly connected with the competition of polyphosphate accumulating organisms (PAOs) and glycogen accumulating organisms (GAOs). Low-temperature EBPR was well-established than hightemperature EBPR. Nevertheless, there was successful EBPR studies at high temperature. Moreover, occasional process upset is crucial and thus became significant to find strategies to favor PAOs population and suppress GAOs population. One of the possible means is through variation of carbon source fed into EBPR system. GAOs typically are slower at consuming propionate than PAOs while both could uptake acetate rapidly. Thus, acetate-fed and propionate-fed culture would be used to investigate the effect of different carbon sources such as VFAs on EBPR. In this study, mixed carbon sources namely acetate, propionate, butyrate, valerate and their iso-forms would be discussed. Batch studies would be conducted under alternating anaerobic-aerobic phases for fermented liquid, mixed carbon sources of (C2+C3), (C2+C3+C4+C5) and (C2+C3+ISOC4+ISOC5). The tests were designed to determine the impact of VFAs on acetate and propionate-fed cultures (C2 and C3 culture) at 25oC and 30oC. It was found out that all except ISO-valeric acid was completely depleted at both temperature. Propionate was the most favorable carbon substrate for C2 and C3 culture at both temperature. Acetate and Butyrate were equally good carbon sources while the presence of other carbon substrates could retard the uptake of acetate. Furthermore, higher temperature was found out to accelerate the process of carbon uptake. At high temperature, P-uptake rate was observed to be higher and able to attain a lower P-concentration at the end of aerobic phase than low temperature. On the other hand, PHA synthesis from the carbon sources was also discussed. PHB formed the major components of PHA for fermented liquid on C2 culture and C2+C3+ISOC4+ISOC5 on C2 Culture, whereas PHV formed the major components of PHA for other batch experiments. At the end of the study, the analysis would suggest the feasibility of high temperature EBPR and its feeding configuration in tropical climate.